Integration of an N-Heterocyclic Carbene Precursor into a Covalent Triazine Framework for Organocatalysis - Troschke, Erik; Khoa Dang Nguyen; Paasch, Silvia; Schmidt, Johannes; Nickerl, Georg; Senkovska, Irena; Brunner, Eike; Kaskel, Stefan (Chemistry - A European Journal, 2018)
The successful incorporation of a thermally fragile imidazolium moiety into a covalent triazine framework resulted in a heterogeneous organocatalyst active in carbene-catalyzed umpolung reaction. The structural integrity of the imidazolium moiety was confirmed by combining solid-state NMR and XPS experiments.
CRIS-Team Scopus Importer:2022-04-14
Keywords: covalent triazine frameworks; microporous materials; N-heterocyclic carbenes; organocatalysis; porous polymers